Advances in Traditional Chinese Medicine research in diabetic kidney disease treatment - Shiyi Shen; Huiyun Zhong; Xiaoshi Zhou; Guolin Li; Changji Zhang; Yulian Zhu; Yong Yang (Taylor & Francis Group, 2024)
AbstractContext Diabetic kidney disease (DKD) is a prominent complication arising from diabetic microangiopathy, and its prevalence and renal impact have placed it as the primary cause of end-stage renal disease. Traditional Chinese Medicine (TCM) has the distinct advantage of multifaceted and multilevel therapeutic attributes that show efficacy in improving clinical symptoms, reducing proteinuria, protecting renal function, and slowing DKD progression. Over recent decades, extensive research has explored the mechanisms of TCM for preventing and managing DKD, with substantial studies that endorse the therapeutic benefits of TCM compounds and single agents in the medical intervention of DKD.Objective This review lays the foundation for future evidence-based research efforts and provide a reference point for DKD investigation.Methods The relevant literature published in Chinese and English up to 30 June 2023, was sourced from PubMed, Cochrane Library, VIP Database for Chinese Technical Periodicals (VIP), Wanfang Data, CNKI, and China Biology Medicine disc (CBM). The process involved examining and summarizing research on TCM laboratory tests and clinical randomized controlled trials for DKD treatment.Results and conclusions The TCM intervention has shown the potential to inhibit the expression of inflammatory cytokines and various growth factors, lower blood glucose levels, and significantly affect insulin resistance, lipid metabolism, and improved renal function. Furthermore, the efficacy of TCM can be optimized by tailoring personalized treatment regimens based on the unique profiles of individual patients. We anticipate further rigorous and comprehensive clinical and foundational investigations into the mechanisms underlying the role of TCM in treating DKD.